2007
DOI: 10.2500/ajr.2007.21.2966
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Extract Induces Cytotoxicity on Human Nasal Epithelial Cells

Abstract: CSE induces cytotoxicity on primary human nasal epithelial cells and the morphological findings closely mimic partition apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 16 publications
5
24
0
Order By: Relevance
“…The concentrations of CSE used can range from 100% CSE for 15 minutes [28] to a 1% CSE for 24 hours (in those studies which use a single cigarette to prepare the initial “100%” stock CSE) [29]. A study exposing primary human nasal epithelial cells to CSE for 1 h, 2 h, and 4 h reported a time and dose-dependent cytotoxicity of CSE [30].…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of CSE used can range from 100% CSE for 15 minutes [28] to a 1% CSE for 24 hours (in those studies which use a single cigarette to prepare the initial “100%” stock CSE) [29]. A study exposing primary human nasal epithelial cells to CSE for 1 h, 2 h, and 4 h reported a time and dose-dependent cytotoxicity of CSE [30].…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of CSE used can range from 100% CSE for 15 min [17] to 1% CSE for 24 h (in those studies which use a single cigarette to prepare the initial ''100%'' stock CSE) [27]. Other investigators have prepared CSE using multiple cigarettes ranging from two cigarettes up to as many as five [13,28]. Many of these studies assessed soluble mediator release and a single time point, but two studies highlight that caution is required as CSE can delay LPS-induced release of IL-8 and granulocyte-macrophage colony stimulating factor in primary epithelial cells, but yet it was not abolished completely at later time points [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Activated NF-kB can have pro-apoptotic effects in certain cells, yet be protective of apoptosis in others [11]. CSE has been reported to induce apoptosis in PBECs [12] and primary nasal epithelial cells by some [13], but not by other investigators [10]. Furthermore, recent research using PBECs indicated that CSE induces necrosis rather than apoptosis [14].…”
mentioning
confidence: 99%
“…Exposure to CS is associated with nasal inflammation (Lee and Kim, 2013;Lan et al, 2007;Huvenne et al, 2010). A possible role of CS exposure in sinonasal cancer has also been discussed ('t Mannetje et al, 1999;Kuper et al, 2002;Sham et al, 2010;Moon et al, 2010;d'Errico et al, 2013).…”
Section: R4f Smoke and Ths22 Aerosol Exposure And Endpoint Generationmentioning
confidence: 99%